STUDY OF GENETIC STABILITY IN IN VITRO CONSERVED PODOPHYLLUM HEXANDRUM USING RAPD MARKERS - A. Tariq; S. Naz; K. Shahzadi; S. Ilyas; S. Javed (Journal of Animal and Plant Sciences, 2015)
In the present study, micropropagation of Podophyllum hexandrum, an endangered species of Pakistan was carried out on basal media containing different combinations of auxins and cytokinins as an attempt for its conservation. The results showed that the media containing BAP and NAA enhanced shoot induction from rhizome segments. Maximum number of shoots was observed in media having higher concentrations of BAP and NAA i.e. 11.0 mg L-1 and 5.3mg L-1 respectively. On an average 84% test tubes were observed showing initiation of shoots within 24 ± 0.83a days, media containing 3.0 mg L-1IBA was found to be the best for rooting. RAPD analysis using 10-mer primers was also carried out to check genetic stability of the in vitro conserved plants in comparison to the mother plants kept in the green house as the control. The results showed no genetic alterations when compared in term of number of bands and their respective sizes thus confirming that the plants conserved in vitro did not go through any genetic changes.
Keywords: Podophyllum hexandrum; in vitro conservation; Genetic stability; molecular markers; RAPDs